18O and 226Ra in the Minjiang River estuary, China and their hydrological implications. (5th May 2016) - Liu, Huatai; Guo, Zhanrong; Gao, Aiguo; Yuan, Xiaojie; Zhang, Bin
Abstract: In this work, the 2 H, 18 O and 226 Ra values in groundwater and surface water in the Minjiang River estuary were investigated in the dry and wet seasons. The δ 18 O values in the dry season were always higher than those in the wet season in both groundwater and surface water because of the presence of evaporation in the water cycle process. During the dry season, the δ 18 O values in groundwater on the southern bank of the Minjiang River are much higher than those on the northern bank because evaporation is more intense in the farmland of the southern bank than in the urbanized northern bank. The δ 18 O values in the estuarine water exhibit a good positive correlation with salinity, with a coefficient of 0.96 (p = 0.05) in both seasons. The 226 Ra activities in the estuarine water increase with increasing salinity because of desorption from riverine suspended particles. The 226 Ra activity reaches a peak value at a salinity of 20.5. Based on a three-endmember model, the average proportions of the estuarine water are calculated to be 0.02 for groundwater, 0.39 for river water and 0.59 for seawater. From this mixing ratio, the groundwater discharge into the estuary is estimated to be 9.31 × 10 6  m 3  d −1 in the wet season.